Causes and management of nutritional rickets among paediatric age group in Rajasthan: a randomised control trial - Atal, Pinky; Aloria, Jitendra; Chaudhary, Meenakshi; Gosaliya, Mahendra; Patni, Aaditya (International Journal of Research in Medical Sciences, 2022)
Background: Rickets disease frequently caused by insufficient of vitamin D. Nevertheless, subsequent researchers have attributed it to a calcium insufficiency throughout the eating plan. There is very little data on the relative efficacy of calcium, vitamin D, or both in the treatment of rickets. The goal of this study was to see if calcium, vitamin D, or a combination of the two may help young infants with nutritional rickets. Methods: 100 patients of nutritional rickets aged 6 months to 5 years were randomly assigned to receive vitamin D (6,00,000 IU single intramuscular injection), calcium (75 mg/kg/day elemental calcium orally) or a combination. All of the participants’ demographics, nutritional status, dietary calcium, and phytate consumption were evaluated. Results: More than 80 percent of the patients in the study had 25OHD levels below 20 ng/ml. Rickets was discovered as an afterthought throughout the remaining 60. Lower respiratory illness (40), upper respiratory tract illness (10) and acute gastroenteritis have been the presenting conditions. Conclusions: Children experiencing rickets exhibited low vitamin D levels in their blood as well as a low calcium intake from their nutrition. When compared to either vitamin D or calcium alone, the combination showed the best therapeutic effect.